2018
DOI: 10.1126/scisignal.aav4285
|View full text |Cite
|
Sign up to set email alerts
|

Going nuclear with stress

Abstract: A mitochondrial-derived peptide regulates nuclear gene expression in response to metabolic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It acts as a regulator of metabolic homeostasis that can prevent diet-induced obesity and insulin resistance, and age-dependent insulin resistance in mice (99101). Notably, MOTS-c can translocate to the nucleus upon cellular stress to regulate adaptive nuclear gene expression by interacting with other stress-responsive transcription factors including nuclear factor erythroid 2-related factor 2 (NFE2L2/NRF2) and binding to chromatin (102104). HEK293 cells that over-express MOTS-c were significantly protected against metabolic stress ( i.e ., glucose and serum deprivation) (102).…”
Section: Cell-autonomous Mitochondrial Communication and Agingmentioning
confidence: 99%
“…It acts as a regulator of metabolic homeostasis that can prevent diet-induced obesity and insulin resistance, and age-dependent insulin resistance in mice (99101). Notably, MOTS-c can translocate to the nucleus upon cellular stress to regulate adaptive nuclear gene expression by interacting with other stress-responsive transcription factors including nuclear factor erythroid 2-related factor 2 (NFE2L2/NRF2) and binding to chromatin (102104). HEK293 cells that over-express MOTS-c were significantly protected against metabolic stress ( i.e ., glucose and serum deprivation) (102).…”
Section: Cell-autonomous Mitochondrial Communication and Agingmentioning
confidence: 99%
“…[6,8] We have recently reported that one particular MDP, MOTS-c (mitochondrial open reading frame of the 12S ribosomal RNA type-c), can translocate to the nucleus to regulate adaptive gene expression in response to cellular stress. [9][10][11][12] Here, we discuss the implications of MOTS-c, a mitochondrial-encoded regulator of the nuclear genome, and propose that the dual mitonuclear genomes should be considered a singular genetic system that is coordinated through dynamic intergenomic communication using reciprocal gene-encoded regulators. We suggest a more inclusive approach to gene network analyses for basic research and therapeutic development.…”
Section: Introductionmentioning
confidence: 99%